A recent update on the morphological classification of intraductal papillary neoplasm of the bile duct: Correlation with postoperative prognosis and pathological features. - Daisuke Noguchi; Naohisa Kuriyama; Yuji Kozuka; Haruna Komatubara; Tatsuya Sakamoto; Takahiro Ito; Aoi Hayasaki; Yusuke Iizawa; Takehiro Fujii; Akihiro Tanemura; Yasuhiro Murata; Masashi Kishiwada; et al. (PLoS ONE)
Purpose We proposed a novel morphological classification for intraductal papillary neoplasm of the bile duct (IPNB) and evaluated its association with postoperative prognosis. Methods Forty-two IPNB patients who underwent surgical resection were classified morphologically into three types-branched (n = 10), main duct (n = 26), and mixed (n = 6)-based on preoperative imaging features indicating cystic and/or bile duct involvement. Among them, 32 patients with evaluable specimens were further categorized pathologically into Type 1 (n = 10) and Type 2 (n = 22). Patient characteristics and postoperative outcomes were analyzed. Results Intraepithelial neoplasia was more frequently observed in the branched type, whereas invasive carcinoma predominated in the main duct type. In the mixed type, a half of patients involved both intra- and extrahepatic bile ducts, and this type also showed the highest incidence of residual tumor. The mixed type had the poorest 5-year postoperative survival rate (50%), compared to 90% in the main duct type and 100% in the branched type. It also exhibited the highest 5-year recurrence rate (62%). Among IPNB patients with associated invasive carcinoma, tumor infiltration beyond the bile duct wall (p < 0.001) and lymph node metastasis (p = 0.021) were significantly associated with poor prognosis, whereas the anatomical extent of the lesion (intrahepatic, extrahepatic, or both) was not. Morphological classification was significantly correlated with pathological subtypes: the branched type was predominant in Type 1 (60%), while the main duct type predominated in Type 2 (64%) (p = 0.039). Conclusions Our novel morphological classification of IPNB correlates with postoperative prognosis and may assist in preoperative planning of surgical strategies for IPNB patients.